1994
DOI: 10.1007/bf01299209
|View full text |Cite
|
Sign up to set email alerts
|

On the efficacy of distributed simplex algorithms for linear programming

Abstract: Dedicated to Professor George B. Dantzig on the occasion of his eightieth birthday.Abstract. We consider the use of distributed computation to solve general unstructured linear programs by the inherently serial approach of the simplex method. Timing models for the distributed algorithms are presented to predict results which are then verified empirically. Our results contribute to the identification of all viable exploitations of distributed computing which is likely to become a prevalent environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Their parallel algorithm divides the columns of the constraint matrix among many processors. Ho and Sundaraj [25] compared the problem of distributed computation of the simplex method using two different methods: (i) distributed reinversion (DINV) and (ii) distributing pricing (DPRI).…”
Section: Related Workmentioning
confidence: 99%
“…Their parallel algorithm divides the columns of the constraint matrix among many processors. Ho and Sundaraj [25] compared the problem of distributed computation of the simplex method using two different methods: (i) distributed reinversion (DINV) and (ii) distributing pricing (DPRI).…”
Section: Related Workmentioning
confidence: 99%
“…The first attempt to exploit task parallelism in the revised simplex method was reported by Ho and Sundarraj (1994). In addition to the natural data parallelism of (column-wise) PRICE, Ho and Sundarraj identified that INVERT can be overlapped with simplex iterations.…”
Section: Task and Data Parallel Revised Simplexmentioning
confidence: 99%
“…Then, if SP 1 generates no proposals for SP 2 during the next cycle (implying W 1 ϭ 0), the algorithm, which has now reverted to DND, would have stopped incorrectly. Ho and Sundarraj [1994] have shown that solution times for LP problems can be reduced when reinversions are overlapped with the simplex steps (by using an extra node). Here, we propose a similar idea-namely, that of performing reinversions when a node is idle.…”
Section: Syncmentioning
confidence: 99%